Cancer treatment associated cardiac toxicities - Chang, Eric Y.; Chaudhry, Aneese F.; Lopez, Victoria; Jain, Sanjay R. (International Journal of Basic & Clinical Pharmacology, 2018)
Cardiovascular disease remains the leading cause of mortality and morbidity in men and women both in the US and worldwide. With increased access to healthcare, it is predicted that life expectancies in developed countries will continue to rise and thus, lead to an increase in both cardiovascular disease and cancer. Similarly, improved survival rates in cancer patients have led to an increased awareness of the presence and potential worsening of cardiovascular disease in these patients. Cardiovascular complications due to side effects from cancer therapy or from cancer progression can be a common occurrence. Although recent advances in cancer therapeutics have led to improved survival rates and quality of life, the increase in life expectancy may be counteracted by the increased morbidity and mortality from progressive cardiac pathology. Examples of such complications include local invasion or distant metastatic spread, which can lead to superior vena cava syndrome, cardiac tamponade, or hyperviscosity syndromes. In addition, many chemo and radiation therapies can be directly toxic to the cardiovascular system. This review aims to discuss the potential cardiac toxicities of the most commonly used chemotherapeutics along with some strategies to manage these complex patients.